The effect of carbon and magnetic nanoparticles on the properties of chitosan-based neural tubes: Cytotoxicity, drug release, In Vivo nerve regeneration - Liudmyla Sukhodub; Mariia Kumeda; Leonid Sukhodub; Oleksandr Tsyndrenko; Oleksandr Petrenko; Volodymyr Prokopiuk; Anton Tkachenko (Carbohydrate Polymer Technologies and Applications)
This study aims to determine the effect of nanoparticles (NPs), namely graphene oxide (GO), multilayer carbon tubes (MWCNTs + Fe), magnetite (Fe3O4) and in situ forming brushite (DCPD) in chitosan (CS) based matrices on the cytotoxicity, Pregabalin (PG) release, and in vivo behavior of mechanically stabilized conductive nerve conduits (NCs). NPs change the composites’ hydrophilicity in the order: DCPD (46.8) < MWCNT (54.21) ∼ Fe3O4 (54.44) < GO (65.99) and the water contact angle (47–66°) corresponds to the conditions of cell adhesion. NPs of ≤ 150 μg/ml reduce cell adhesion but don't trigger oxidative stress and toxic effects. Magnetite NPs of 300 µg/ml promote apoptosis in nerve cells. The introduction of PG at stage b during the DCPD formation provides the drug release kinetics closest to the zero-order kinetic model. The most electrically conductive GO- and MWCNTs + Fe - containing NCs have a prolonged biodegradation period of about 6 months, which makes them promising for the regeneration of damaged peripheral nerves in humans.